Kesiapan Menikah dalam Perspektif Psikologi Pendidikan Islam - Supono, Eko; Rohimah, Siti (Lembaga Yasin AlSys, 2026)
Readiness for marriage is a multidimensional construct encompassing psychological, emotional, spiritual, social, and economic maturity which, from the perspective of Islamic Educational Psychology, is understood not only as physical and psychological readiness but also as readiness in terms of morals (akhlak), faith (iman), and social responsibility in accordance with shari‘ah guidelines. This article aims to analyze the concept of marital readiness through the lenses of general psychology and Islamic Educational Psychology, and to explain how Islamic education contributes to shaping personal maturity prior to entering married life. A descriptive qualitative approach was employed using a literature review of relevant works on marital readiness, developmental psychology, and Islamic education. The findings show that marital readiness in Islamic Educational Psychology comprises five main dimensions: (1) psychological maturity; (2) the ability to regulate emotions; (3) spiritual readiness; (4) social maturity; and (5) continuous moral education. The implications of this study underscore the crucial role of family education and Islamic educational institutions in instilling Islamic values, emotional regulation skills, and interpersonal competencies as an integrative provision for Muslim individuals before entering married life.